Javanese Altruism: Suicide as a Symbol of Political Resistance in Modern Javanese Theatre - Novianto, Wahyu; Guntur, Guntur; Jamal, Jamal; Murtono, Taufik; Dayari, Achmad; Aji Kus Indriani, Arrauna Bening (Institut Seni Indonesia Yogyakarta, 2025)
In this research, the representation of suicide in modern Javanese theatre is analyzed as a symbol of resistance against repressive power, with an emphasis on the altruistic values typical of Javanese culture. Two theatre scripts, KUP (Sego Gurih Theatre Company) and Dumeh (Sedhut Senut Theatre Company), are the focus of this study because they feature main characters who choose suicide. A hermeneutic approach within an interpretive framework and content analysis of the texts have been used. This method finds that suicide in both texts is not meant as a personal act of despair, but rather as a political and spiritual statement grounded in the ethics of self-sacrifice in Javanese cosmology. In this context, harmony, obedience, and self-control assume a resistance-oriented connotation. Modern Javanese-language theatre, therefore, is positioned as a space for emancipatory social critique. Thus, suicide is understood not merely as a tragic act, but as a dramatic and political strategy used to uphold justice and restore collective dignity. This research contributes to studying Javanese culture and theatrical practice as a medium for contemplating the relationship between the body, power, and spirituality.